2018
DOI: 10.1128/genomea.01567-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Sweet potato feathery mottle virus and Sweet potato virus G from Brazil

Abstract: In Brazil, Potyvirus species in sweet potatoes have been detected mostly by serology. Here, we report the complete genome sequences of two Potyvirus species, Sweet potato feathery mottle virus strain (SPFMV-UNB-01) and Sweet potato virus G strain (SPVG-UNB-01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…At present, 35 viral species have been reported to infect sweet potato crops worldwide (Souza et al, 2018) which comprises the major biotic constraint on sweet potato production worldwide. In 2005, 10-60% viral disease incidence was observed in sweet potato fields (Prasanth & Hegde, 2008) and the field monitoring indicated that 58% of plants were found to be virusinfected.…”
Section: Introductionmentioning
confidence: 99%
“…At present, 35 viral species have been reported to infect sweet potato crops worldwide (Souza et al, 2018) which comprises the major biotic constraint on sweet potato production worldwide. In 2005, 10-60% viral disease incidence was observed in sweet potato fields (Prasanth & Hegde, 2008) and the field monitoring indicated that 58% of plants were found to be virusinfected.…”
Section: Introductionmentioning
confidence: 99%